2022
DOI: 10.1007/s11356-021-18407-0
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of E. coli O157:H7 in urban recreational waters from Spring and Autumn: a comparison analysis

Abstract: Persistence of E. coli O157: H7 (EcO157) in 48 water samples (24 Spring samples and 24 Autumn samples) from 3 urban recreational waters in Changchun City was investigated, and multivariate statistical analysis was performed to correlate survival data with water physicochemical properties and bacterial communities. Our data showed that EcO157 survived longer in Spring samples than in Autumn samples regardless of the lakes. Results revealed that recreational water physicochemical properties and bacterial communi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The transmission of E. coli O157:H7 through water has been documented in various settings, including both drinking water that has been contaminated [56] and recreational water bodies [57,58]. Furthermore, studies conducted in Nigeria and South Africa demonstrated that water used for irrigation had notable influence on the dissemination of E. coli O157:H7 through the contamination of food products [59,60].…”
Section: Contaminated Water As a Transmission Vectormentioning
confidence: 99%
See 2 more Smart Citations
“…The transmission of E. coli O157:H7 through water has been documented in various settings, including both drinking water that has been contaminated [56] and recreational water bodies [57,58]. Furthermore, studies conducted in Nigeria and South Africa demonstrated that water used for irrigation had notable influence on the dissemination of E. coli O157:H7 through the contamination of food products [59,60].…”
Section: Contaminated Water As a Transmission Vectormentioning
confidence: 99%
“…Untreated sewage released from hospitals, farms, and residential areas containing E. coli O157:H7 into nearby water bodies also increases the risk of human infections significantly [61]. Based on the evidence, E. coli O157:H7 easily survives in water and may persist for several weeks and even longer [58]. Strong rainstorms may cause sediments to be re-suspended, which could lead to an abrupt rise in E. coli O157:H7 concentrations in the water [62].…”
Section: Contaminated Water As a Transmission Vectormentioning
confidence: 99%
See 1 more Smart Citation